Interpreting Teaching STEM Education to Pre-service Elementary Teachers Through Online Course - Nuraeni, Fitri; Putri, Hafiziani Eka; Majid, Nuur Wachid Abdul; Iskandar, Sofyan (KnE Social Sciences, 2024)
Insufficient comprehension of integrated STEM learning has become one of the main difficulties for teachers in implementing STEM lessons at school due to lack of integrative STEM curriculum in teachers’ education programs. Therefore, the Elementary Teacher Education Program Universitas Pendidikan Indonesia in Purwakarta offers STEM Education for Elementary course as an optional course to support 21st-century education at the elementary school level. However, due to the continued Covid-19 pandemic, during the second semester of the academic year 2020/2021, all courses in our program were entirely carried out online. Through the descriptive analysis method, this paper details how the 16-weeks course was enacted online with a varied delivery form. Forty-two pre-service teachers enrolled in the course. Data on the course implementation were gathered in the form of video recordings of the lesson, while students’ perception of the course delivery was captured through a course evaluation questionnaire. Results imply that the course includes a theoretical and practical session with teaching simulations and engineering challenges to model STEM teaching and learning to develop pre-service teacher’s STEM pedagogical and content knowledge. In addition, course evaluation suggests that after enrolling in the course, the pre-service teacher has positive perceptions of the course delivery. Keywords: STEM education, pre-service elementary teachers, online course